Educação para o plurilinguismo no trabalho com estudantes migrantes e refugiados: experiências de docentes de escolas públicas de Roraima - Nilmara Milena da Silva Gomes (2024)
Public schools in Roraima, particularly within the Municipal and State Education Networks, have received, in recent years, several hundred migrant and refugee students (Zambrano, 2021; Cavalcanti et al., 2021). Focusing on this environment, as well as on interviews with four teachers and the didactic materials they provided, this research aims to analyze whether the initiatives undertaken can favor the inclusion of migrant and refugee students in the basic education schools where they work, guided by the theoretical framework of plural approaches. The following steps were outlined in order to achieve this goal: a) identifying, from the teachers interviews, their motivations for the development of activities that could promote welcoming actions for migrant and refugee students in their classes; b) examining what the teachers report about the ways in which languages are, or are not, mobilized in their courses and c) analyzing whether the actions reported by the teachers do or do not favor the welcoming of migrant and refugee students in basic education schools. The theoretical framework of Indisciplinary Applied Linguistics (Moita Lopes, 2006), Portuguese as a Welcoming Language (Amado, 2013; Camargo, 2018; Lopez; Diniz, 2019; Ruano, 2019; Lopez, 2022), the Expanded Model of Linguistic Policy (Shohamy, 2006) and Plural Approaches (Candelier, 2009) were employed to propose guidelines for the construction of horizontal linguistic policies (Bizon; Camargo, 2018) that benefit migrant and refugee students enrolled in basic education. In-depth interviews (Herlinger, 2011) and thematic content analysis (Bardin, 2016) of the teachers’ discourse and their didactic materials revealed three key motivators for a review of the school welcoming process : a) the significant influx of children and adolescents migrating to Roraima, b) experiences of discrimination and xenophobia faced by migrants and refugees in the school setting, and c) the recognition of emotional discomfort these students endure during their migratory process. This study concludes that, despite lacking specialized training, the teachers turned to plural approaches as a strategy to deal with schools' unpreparedness in welcoming migrant and refugee students. As per the interviews and didactic materials, the intercultural approach promoted cross-cultural dialogues, acting to reduce discriminatory and xenophobic behaviors. Concurrently, the intercomprehension between Romance languages improved access to information in the school setting, in addition to reducing the distance between migrant students, refugees, their classmates and teachers. Furthermore, intercomprehension was integrated into mathematics, Portuguese, and arts classes, making the learning process more meaningful not only for migrant and refugee students but also for Brazilians students as well. Nevertheless, it is important to acknowledge that the implementation of these approaches in plurilingual education may face specific challenges and limitations, which should be considered in future investigations.